Turn to Practice Within Working Life Studies - Buch, Anders; Andersen, Vibeke; Klemsdal, Lars (Nordic Journal of Working Life Studies, 2015)
What does practice theory and practice-based studies have to offer working life studies? This is the seminal question this special issue poses. In seven articles, researchers with an affiliation to Nordic working life studies and with a background in practice theory illustrate and reflect on how practice theoretical approaches can help working life studies in better understanding work practices and the material, technological, economic, organizational, and societal conditions that shape and are shaped by these practices. In addition, this issue contains three reviews of recent practice theoretical volumes that strive to theorize (work) practices and assess the merits of practice theoretical perspectives.